Semantics Analysis of Homonym in Konjo Language - Nursanti, Nursanti; Rahmat, Subhan (CV. Strata Persada Academia, 2023)
The Pattallassang Tombolo Pao community is the focus of this research project, which investigates the use of homonyms in the Konjo language and the differences in the meanings of terms used by that community. This study aims to explore specific terms that, despite their seemingly identical spellings and pronunciations, are understood to convey very diverse connotations in the Konjo language. In this study, a descriptive qualitative method was used to conduct research utilizing a case study approach, and a literature review was also conducted. Interviews and written documentation were the methods of data collection for this study. The findings of this study showed that there are 23 homonym words in the Konjo language, which is used by the people who live in the Pattallassang Tombolo Pao community. This research also discovered one homonym with three distinct meanings despite having the exact spelling and sound. This word is called